Interdisciplinary-Based Learning Approach in Producing Competitive Human Resources at State Islamic University - Zulvia Trinova; Wahyuli Lius Zen; Ilpi Zukdi; Hadeli Hadeli; Hidayat Al Azmi (STAI Hubbulwathan Duri, 2023)
The aim of this research is to determine the interdisciplinary approach in higher education so that it can make education more efficient and functional in producing competent human resources. The research method used is field research with a descriptive quantitative approach. The data source, referred to as the respondent, is Semester VII, a state Islamic university in Padang in 2021/2022 as many as 98 students. The form of questionnaire used is a Likert Scale in the form of a continuum consisting of four categories, namely Strongly Agree (SS), Agree (S), Disagree (KS) and Disagree (TS). The results of research on interdisciplinary approaches (educational approaches, curriculum approaches, leadership, economic approaches, and vision approaches) in learning have been able to make students competitive at state Islamic University because they are inspired to learn so that they have broad and complex knowledge needed in this era of globalization, able to solve problems because problems in the era of globalization are not solved with only one knowledge, improve the ability and skills to use information technology. Without these abilities and skills, it is difficult for students to compete with others.